Terminal arbors of axons projecting to the somatosensory cortex of the adult rat. II. The altered morphology of thalamocortical afferents following neonatal infraorbital nerve cut - Jensen, KF (J Neurosci, 1987)
The organization of the whisker representation within the neocortex of the rat is dependent on an intact periphery during development. To further investigate how alterations in this cortical map arise we examined the organization of thalamocortical afferents to the whisker representation in adult animals in which the infraorbital branch of the trigeminal nerve was cut on the day of birth. The disrupted pattern of thalamocortical projections to the vibrissae representation was apparent in the abnormal pattern of the anterograde transport of horseradish peroxidase from the thalamus, as well as in the abnormal pattern of succinate dehydrogenase activity. To determine the morphology of individual thalamocortical axons associated with this disrupted pattern, terminal arbors were “bulk-labeled” by injections of horseradish peroxidase into the white matter beneath the somatosensory cortex. Terminal arbors were identified by their laminar distribution of boutons corresponding to the specific thalamocortical afferent. The medial to lateral extent of these terminal arbors varied dramatically, from 350 to 1500 microns. In addition, terminal arbors innervating the same local area of cortex appeared to have varying degrees of overlap. Thus, the disruption of the neocortical vibrissae representation appears to involve the abnormal arborization of individual thalamocortical afferents. This finding supports the hypothesis that the fine-grain organization of the somatotopic map is dependent on the morphology and organization of individual thalamocortical arbors, which, in turn, are dependent on the periphery during development.